Ghana : Will it Be Gifted or Will it Be Cursed? - Aydin, Burcu (IMF Working Papers; Working Paper, 2011)
Will Ghana's oil production from 2011 accelerate progress toward middle-income status, or will it retard gains in living standards through a possible "resource curse"? This paper examines the likelihood of "resource curse" effects, drawing on a dataset of 150 low and middle income countries from 1973 to 2008 using static and dynamic panel estimation techniques. Results confirm that resource rich countries in Ghana's income range do experience slower growth than their more diversified peers, an effect that appears to be related to weaker governance. Provided that Ghana can preserve and improve its economic governance and also strengthen fiscal management, prospects look good for converting its oil wealth into sustained strong economic growth.